Analysis of spatial pattern and ecological service value changes of large-scale regional paddy fields based on remote sensing data - Liu Yuan; Zhou Qingbo; Yu Qiangyi; Wu Wenbin (智慧农业, 2020)
Under the pressure of economy development and climate change, rice production and distribution in the Yangtze River basin have undergone great changes, which may pose a great threat to the ecological environment and food security. Based on land use remote sensing-monitoring data from1990 to 2015, the GIS spatial analysis method was used to explore the spatial pattern variation characteristics of paddy fields in the Yangtze River economic belt. Meanwhile, Ecosystem services value (ESV) was calculated by using the equivalent factor method corrected by region and time factor to measure the comprehensive impact of paddy field change. The results showed that, to begin with, paddy fields number of the Yangtze River economic belt continued to decrease, with a total decrease of 17 390km2, and the decrease rate presented a trend of growth with significant regional differences. The difference between the reduction rate of paddy fields in the middle upper and the lower reaches of the Yangtze River was about 9.56%. Among them, in the lower reaches of the Yangtze River, the proportion of paddy fields decreased, while in the middle and upper reaches which was just the opposite. Then, paddy fields mainly flowed to construction land and water, resulting from economic construction and aquaculture development. Paddy fields chiefly came from water, dry land and wetland, etc. Furthermore, paddy fields in the Yangtze River Delta, the middle reaches of the Yangtze River and the Chengdu-Chongqing urban agglomerations changed the most dramatically. The expansion of construction land to paddy fields was widespread, and paddy fields flooded by water primarily distributed in the two lake plains. In addition, the conversion of paddy fields and other ecosystems had a positive impact on ESV, in which the paddy-water diversion type contributed the most. Its scale determined the net increase of ESV in different periods. Value loss lead by conversion from water to paddy fields was the largest, and construction land invading paddy fields was the second. The conversions in different cities were different, so the difference in ESV increases and decreases. In addition, the tradeoffs within ecosystem services were mainly between hydrological regulation, water supply and food production, gas regulation, which were directly related to the increase of water resources and the loss of paddy fields. The research results are helpful to reveal the spatio-temporal changes process of paddy fields in the Yangtze River basin and its impact on ecological functions, and provide theoretical support for regional land use planning, agricultural policy and ecological sustainable development.